Electrical Characterization of Ca1-Xaxcu3ti4o12 (A = Sr or Ba) With X = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5 Ceramics - Mustafa, Mazni (2008)
CaCu3Ti4O12 (CCTO) has attracted an attention based on its extraordinary dielectric properties and makes it applicable to a microelectronic device application for capacitive element. Polycrystalline of CCTO, Ca1-xSrxCu3Ti4O12 (CSCTO) and Ca1-xBaxCu3Ti4O12 (CBCTO) with x = 0.1, 0.2, 0.3, 0.4 and 0.5 ceramics oxide were prepared using solid state reaction technique. The XRD patterns for all samples show the single phase peak and the calculated lattice parameter for CCTO is ’a’ = 7.3870 Å. The SEM images show that the grain size was significantly increases with doping and consist of grain and grain boundary. The value of dielectric permittivity of CCTO at 1 kHz increases with temperatures from 2740 at 70 oC to 3560 at 250 oC. The complex impedance plot shows three semicircle arcs indicating that the electrical processes in the material due to the contribution from the grain at high frequencies, the grain boundary at intermediate frequencies and the electrode effect at low frequencies. The behaviour was modeled using equivalent RC circuit consisting of three parallel resistors, R and the universal capacitors, C*. The grain resistance, Rg and the grain boundary resistance, Rgb decrease with temperatures. The conductivity plots for all the samples show two clear regions due to the grain boundaries at low frequency and grain at high frequency. The value of n obtained by fitting the grain region at high frequency dependent decreases with temperatures with the value higher than 0.6 indicating that the conduction is due to hopping of electrons among Ti4+ and Ti3+. A close similarity of the relaxation and conductivity activation energy values indicates that the processes may be attributed to the same type of charge carriers.